Pediatric Pulseless Ventricular Tachycardia: A Simulation Scenario for Fellows, Residents, Medical Students, and Advanced Practitioners - Katherine Cashen; Tara Petersen (Association of American Medical Colleges, 2016)
Abstract Introduction Pulseless ventricular tachycardia is an uncommon presentation to the pediatric emergency department (ED) or the pediatric ICU (PICU); however, if unrecognized or inappropriately treated, it can lead to significant morbidity and mortality. This resource was created to simulate a high-acuity and low-frequency event targeting PICU fellows, pediatric emergency medicine fellows, pediatric residents, ED residents, medical students, and advanced nursing providers. Methods This scenario details the case of a 12-year-old boy with a history of heart transplant who presents with the chief complaint of dizziness. He initially has multiple premature ventricular contractions and then progresses to pulseless ventricular tachycardia due to acute rejection. This simulation may be performed in a simulation lab or in situ in the ICU or ED. Necessary personnel include a simulation technician, instructors, and a nurse. A code cart and defibrillator with hands-free pads appropriate for the mannequin are needed supplies. Critical actions include cardiopulmonary resuscitation, defibrillation with three shocks, and administration of anti-arrhythmic. At the end of the scenario, a formal debriefing and learner assessment with structured feedback are performed. Results Approximately 110 learners have completed this module during 18 separate sessions. Written evaluation from participants (n = 94) using a Likert scale (1 = not at all, 4 = to a great extent) shows that the objectives of the simulation are met to a great extent, with an average score of 3.8. Discussion In conclusion, this resource advances learner knowledge and comfort when managing a pediatric patient with pulseless ventricular tachycardia, reviews appropriate management, and helps identify knowledge deficits in the management of these patients.